Hypocalcemia in Patients With Osteoporosis and Normal Renal Function, Treated With Denosumab, a Retrospective Analysis - Zouheir Ibrahim Bitar; Adnan MA Hajjiah; Ossama Sajeh Maadarani; Mahmoud Mostafa Elzoueiry; Mohamed Refaat Gohar; Mohamad Abdelfatah; Fawaz Alabdali (Nutrition and Metabolic Insights, 2024)
Objective: The reported hypocalcemia in postmenopausal women with osteoporosis who received Denosumab was low (0.05%-1.7% to 7.4%). The major prediction factors were vitamin D and calcium levels and renal function. The objective is to evaluate the incidence of hypocalcemia in patients with osteoporosis, normal renal function, and vitamin D who received Denosumab. Method: A retrospective analysis was conducted using the medical records (2022-2023). We looked for hypocalcemia (albumin-adjusted calcium lower than 2.2 mmol/L). Results: Two hundred one postmenopausal women diagnosed with osteoporosis and received denosumab treatment were included. All patients received vitamin D3 capsules and calcium supplementation. The mean age of the patient was 75.7 ± 7.0 years (56-91 years). Hypocalcemia was observed in 46 (23%) patients following a subcutaneous dose of Denosumab 60 mg. Median calcium was 2.25 mmol/L (minimum: 0.890 mmol/L, maximum: 2.6 mmol/L). Fourteen (30.4%) patients had severe hypocalcemia (<1.8 mmol/L) and required parenteral correction. A comparison between hypocalcemia and patients with normal calcium indicated that the significant predictor of hypocalcemia was pretreatment parathyroid hormone levels (9.9 ± 11.8vs 7.6 ± 2.56 pmol/L, respectively; P  < .005). The prognostic role of parathyroid hormone for the denosumab-associated hypocalcemia was assessed using ROC curve analysis. For the cut-off value of Parathyroid hormone = 6.8 pmol/L, giving serum parathyroid measurement an AUC of 0.668 (0.599-0.737) - P  = .0007; sensitivity 85%; specificity 52%. Conclusion: Hypocalcemia induced by the denosumab treatment is more prevalent than previously shown in patients with osteoporosis receiving adequate calcium and vitamin D supplements. An elevated parathyroid hormone predicts hypocalcemia related to denosumab therapy in patients with normal calcium and vitamin D levels.